Kicked to the Curb: The triangular trade of neoliberal polity, social insecurity, and penal expulsion - Lloyd, Antony C. (International journal of law, crime and justice, 2018)
The slave trade of the 1700s constituted a triangular trade in human cargo. Critically, there is a contemporary triangular trade, the three limbs of which are neoliberal polity; the reproduction of social insecurity; and the modernised transformation of criminal justice and penal policy in the direction of exclusionary punishment and prison. Additionally, the contemporary triangular trade converges in a double fist of negation: the first is the expulsive consequences of the neoliberal order; the second is the response of the criminal justice domain exemplified in retributive punishment and expanding prison populations. The original and timely contribution of this article juxtaposes the two trades, separated by over three hundred years, to allow the former to reach into the present to advance new insights into the latter.